ENGLISH TEACHING INSTRUCTION FOR NON-ENGLISH LEARNERS - Arin Inayah (Universitas Islam Lamongan, 2019)
The quality of educational institutions is influenced by teaching and learning process that is students and lecturers. Novalita (2006) state that to learn a language the learners need more than just once or twice, but they need many time to understand the language, the real meaning of the language, the structure of the language, and so on. There is no good strategies in teaching process, but suitable strategy which is can be used in the teaching process. Therefore, every teacher or lecturer should master many strategies in the teaching and learning process. Some strategies can be applied to some students or learners, but it can’t be applied to all of students or learners. he goal of this study is to observe how the teacher implements English teaching instruction at English language center (PKPBI). Besides that, what are the material used and the way how teacher evaluates and also how do the learners perceive the English teaching instruction at English language center (PKPBI) of Maulana Malik Ibrahim state Islamic university of Malang. This study was a qualitative research because this study is a case study which focuses on teaching process. The data collections used in this study were observation, interview, and documentation. In order to analyze the data collected in the research project and answer the core questions of the study, it was used the grounded theory. The researcher found that the contents of the material used was reading section characterized by provision of an English reading text on mathematic-content-related area followed by writing exercises. The teacher implement English teaching instruction with the aim of answering the question, it can be concluded that for the beginning of teaching, there were a big amount of mistakes with the guidance and no explicit implementation of grammatical aspects during the lessons, because the teacher intents to present language items as in a regular language course. The balance between content and language was not easy to manage either, because in some situations the teacher tends to focus more in language or in content. The teacher evaluate by her choice of evaluation. She felt confused and scared at the beginning of the experience. About perceiving of the learners, the researcher concluded that the students feel challenging with the process of teaching and learning in the class, they also interesting with because they can continued applied what they learn. Key words: Teaching instruction, Non-English learners